Investigation of NEAT1, IFNG‐AS1, and NRIR expression in Crimean–Congo hemorrhagic fever. Issue 6 (1st November 2020) - Bayyurt, Burcu; Bakir, Mehmet; Engin, Aynur; Oksuz, Caner; Arslan, Serdal
Abstract: Crimean–Congo hemorrhagic fever (CCHF), whose causative agent is CCHF orthonairovirus (CCHFV), demonstrates different symptoms in patients. Long noncoding RNAs (lncRNAs) take part in various pathological processes of viral diseases. They are prominent regulators of antiviral immune responses. To our knowledge, this study is the first study to investigate nuclear paraspeckle assembly transcript 1 (NEAT1), interferon (IFN) gamma antisense RNA 1 (IFNG‐AS1), and negative regulator of IFN response (NRIR) expression in CCHF in the literature. We selected these lncRNAs because they are related to IFN signal or IFN‐stimulated genes. We investigated NEAT1, IFNG‐AS1, and NRIR gene expression in patients with CCHF. Total RNA was extracted from blood samples of 100 volunteers and NEAT1, IFNG‐AS1, and NRIR expression were measured using a quantitative real‐time polymerase chain reaction. NRIR expression was statistically significant in cases versus controls ( p < .001), fatals versus controls ( p < .001), and fatals versus nonfatals ( p = .01). Furthermore, NRIR was found statistically significant at some clinical parameters including alanine aminotransferase ( p = .03), international normalized ratio ( p = .03), prothrombin time ( p = .02), and active partial thromboplastin time ( p = .01) in CCHF cases. NEAT1 and IFNG‐AS1 expression were downregulated in the case and fatal groups which were compared with controls. Our results demonstrate that NRIR may be important in CCHF pathogenesis and the target of CCHF treatment. Highlights: This study is the first to investigate some long noncoding RNAs (NEAT1, IFNG‐AS1 and NRIR) expression in host after CCHF infection. NRIR up regulation is statistically significant in CCHF patients and fatals. NRIR expression was also found to be associated with clinical parameters in CCHF pathogenesis. NRIR can be important molecular marker and therapeutic target in CCHF disease progression.